Answer:
Correct
Step-by-step explanation:
Answer:
AEG - BEA = BEG => 81-27=54
Step-by-step explanation:
Answer:
w = 3
Step-by-step explanation:
19w - 1 = 11w + 23
19w - 11w = 23 + 1
8w = 24
w = 3
Using the given information we found that the equation of the parabola is:
y = (-4/9)*(x - 3)^2 + 5
And its graph is below.
<h3>
How to get the equation of the parabola?</h3>
For a parabola with vertex (h, k), the equation is:
y = a*(x - h)^2 + k
Here the vertex is (3, 5), so the equation is:
y = a*(x - 3)^2 + 5
And the y-intercept is y = 1, this means that:
1 = a*(0 - 3)^2 + 5
1 = a*9 + 5
1 - 5 = a*9
-4/9 = a
So the parabola is:
y = (-4/9)*(x - 3)^2 + 5
And its graph is below.
If you want to learn more about parabolas, you can read:
brainly.com/question/1480401